BL_GERICHTE 410 16 294 vom 11. Oktober 2016 - BL Gerichte (2016)
Zivilprozessrecht Vollstreckung von Entscheiden: Taxation nach Art. 345 Abs. 1 lit. b ZPO/Ordnungsbusse nach Art. 343 Abs. 1 lit. c ZPO